2020
DOI: 10.21203/rs.2.24026/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FGF21 alleviates neuroinflammation following ischemic stroke by modulating the temporal and spatial dynamics of microglia/macrophages

Abstract: Background: Resident microglia and macrophages are the predominant contributors to neuroinflammation and immune reactions, which play a critical role in the pathogenesis of ischemic brain injury. Controlling inflammatory responses is considered a promising therapeutic approach for stroke. Recombinant human fibroblast growth factor 21 (rhFGF21) has anti-inflammatory properties by modulating microglia and macrophages, but our knowledge of the inflammatory modulation of rhFGF21 in focal cerebral ischemia is lacki… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Peroxisome proliferator‐activated receptor gamma (PPARγ) belongs to a superfamily of nuclear receptors that contribute to antioxidant and anti‐inflammatory responses 46 . PPARγ agonists such as rosiglitazone 47 or PPARγ activating factors, such as 1, 25‐dihydroxyvitamin D3 (1, 25‐D3), recombinant human fibroblast growth factor 21 (rhFGF21), and oleic acid 48‐50 attenuate brain inflammation and protect against ischemic injury in murine models of stroke. Specifically, microglia respond with a decrease in M1 phenotypic markers and a parallel increase in M2 markers after PPARγ activation.…”
Section: Microglial Polarization and Their Modulatory Mechanisms Aftementioning
confidence: 99%
“…Peroxisome proliferator‐activated receptor gamma (PPARγ) belongs to a superfamily of nuclear receptors that contribute to antioxidant and anti‐inflammatory responses 46 . PPARγ agonists such as rosiglitazone 47 or PPARγ activating factors, such as 1, 25‐dihydroxyvitamin D3 (1, 25‐D3), recombinant human fibroblast growth factor 21 (rhFGF21), and oleic acid 48‐50 attenuate brain inflammation and protect against ischemic injury in murine models of stroke. Specifically, microglia respond with a decrease in M1 phenotypic markers and a parallel increase in M2 markers after PPARγ activation.…”
Section: Microglial Polarization and Their Modulatory Mechanisms Aftementioning
confidence: 99%
“…These studies have demonstrated crosstalk between FGF21 and the nervous system. In turn, during some harmful events related to the nervous system, such as TBI, I/R injury, cognitive impairment and neurodegenerative diseases (Chen et al 2018 ; Wang et al 2018b ; Kang et al 2020 ; Jiang et al 2019 ; Wang et al 2020 ), FGF21 can also exert certain protective effects. Nevertheless, whether FGF21 has certain protective effects in ICH injury has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Human fibroblast growth factor 21 (FGF21) is an endocrine member of fibroblast growth factor family that plays important role in glucose metabolism, lipid metabolism and energy balance [77][78][79]. Previous study demonstrated that the anti-inflammatory effect of recombinant FGF21 on transient focal cerebral ischemia and reperfusion occurs through regulation of microglia and peripheral macrophages via NF-κB and PPARγ signaling pathway [80]. Moreover, recombinant FGF21 has been showed protective effects on acute BBB damage following diabetic stroke through increasing PPARγ activity and upregulation of BBB junctional complex proteins [81].…”
Section: Anti-inflammatorymentioning
confidence: 99%